Environmental impact assessment of an Italian vertically integrated broiler system through a Life Cycle approach. (1st February 2017) - Cesari, V.; Zucali, M.; Sandrucci, A.; Tamburini, A.; Bava, L.; Toschi, I.
Abstract: Poultry meat represents one of the most popular meat products in the world and its production is expected to increase significantly in the next decades. The Italian broiler sector is characterized by a vertically integrated intensive production system and a high final weight of broilers in comparison to the other European countries. The Life Cycle Assessment method was used to estimate environmental impacts (Global Warming Potential; Acidification; Eutrophication; Terrestrial ecotoxicity; Non-renewable fossil energy) of 1 kg of broiler carcass weight at slaughterhouse gate in an Italian integrated broiler group. Moreover, the effects of final live weight and stocking density on the impacts were studied. Broiler fattening resulted the most impactful phase for all the impact categories, contributing on average for 87% of impacts. Conversely, the hatchery, breeder rearing and slaughtering phases moderately concurred to impact categories. Heavy broilers (roasters) showed the higher impacts per kg live weight compared to light and medium live weight broilers mainly due to the worse feed conversion ratio. The main contribution to environmental impacts in the fattening phase was feed production and processing; in particular purchased protein feeds, mainly soybean meal, were the greatest single contributor to all impact categories. The reduction of final live weight of Italian broilers from 2.6 kg to 1.6 kg could lower the total Global Warming Potential of the Italian broiler sector by about 12%. In the scenario analysis the increasing stocking density up to the maximum allowed determined only slight effects on the environmental impacts per kg carcass weight. Highlights: The Italian broiler production is characterized by a vertically integrated system. A Life Cycle Analysis of broiler production at slaughterhouse gate was performed. Purchased protein feeds, mainly soybean, strongly contributed to impacts. Lowering final weight could mitigate Global Warming Potential of the broiler sector. In high stocking density scenario impacts on carcass weight were slightly modified.